Implementation of Hifdz ad-dien in Preserving the Existence of Sharia Life Insurance in Indonesia - Harahap, Nurhayati; Soemitra , Andri; Rokan, Mustafa Khamal; Yusoff , Murni (UPT Publikasi Ilmiah UNISBA, 2025)
This study explores the implementation of Hifdz ad-Dien (protection of religion), one of the core objectives of Maqasid al-Shariah, in preserving the existence and development of Sharia life insurance in Indonesia. As a financial instrument rooted in Islamic principles, Sharia life insurance (soul) not only provides economic security but also reflects a commitment to religious values by avoiding elements prohibited in conventional insurance, such as riba (interest), gharar (uncertainty), and maisir (gambling). The research examines how Hifdz ad-Dien functions as both a spiritual and practical framework that encourages Muslim communities to engage with Sharia-compliant financial products. By analyzing the role of religious scholars, fatwa institutions, and public perception, this study highlights the theological, legal, and socio-cultural factors that contribute to the sustainability of Sharia life insurance in Indonesia. The findings suggest that strengthening religious literacy and promoting the alignment of insurance practices with Islamic values are essential in enhancing public trust and ensuring the long-term viability of Sharia insurance.